Exploration of Potential Molecular Targets of Dexmedetomidine in the Intestinal Repair of Burnt Rats [Erratum] - Qin C; Jiang Y; Yu M; Bian Y; Yu Y (Dove Medical Press, 2021)
Qin C, Jiang Y, Yu M, Bian Y, Yu Y. J Inflamm Res. 2021;14:3197–3206. The authors have advised the affiliation numbers are missing from the author list on page 3197. This error was introduced by the Editorial staff during the publication process. The correct author list and affiliations are as follows. Chao Qin1-3,* Yi Jiang1,2,* Mingdong Yu1,2,* Yingxue Bian4 Yonghao Yu1,2 1Department of Anesthesiology, Tianjin Medical University General Hospital, Tianjin, 300052, People’s Republic of China; 2Tianjin Institute of Anesthesiology, Tianjin, 300052, People’s Republic of China; 3State Key Laboratory of Medicinal Chemical Biology (Nankai University), Tianjin, 300071, People’s Republic of China; 4Department of Anesthesiology, Tianjin Union Medical Center, Tianjin, 300121, People’s Republic of China *These authors contributed equally to this work Read the original article